2006
DOI: 10.1159/000091686
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Lipid Profile by Amaranth <i>(Amaranthus esculantus)</i> Supplementation in Streptozotocin-Induced Diabetic Rats

Abstract: Background/Aims: Lipid disorders may exacerbate some complications of diabetes. Amaranth has been reported to exhibit a cholesterol-lowering effect in hyperlipidemic animals. The present study was designed to investigate the effect of amaranth on serum glucose and the lipid profile in diabetic rats. Methods: Male Sprague-Dawley rats were assigned to normal control, diabetic control, diabetic amaranth-grain (AG)-supplemented (500 g/kg diet) and diabetic amaranth-oil (AO)-supplemented (90 g/kg diet) groups and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Conforti and others (2005) detected antidiabetic activity in 2 varieties of A. caudatus seeds using an in vitro assay consisting of the inhibition of α‐amylase, which acts in the digestion of starch and reduces the absorption of glucose. Using streptozotocin‐induced diabetic rats, Kim and others (2006a,b) investigated the effect of amaranth oil and grain supplementation ( A. esculentus L.) on blood glucose and the lipid profile. The rats were divided into 4 groups: normal control, diabetic control, diabetic group supplemented with amaranth grain, and diabetic group supplemented with amaranth oil for 3 wk.…”
Section: Action On Blood Glucose Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforti and others (2005) detected antidiabetic activity in 2 varieties of A. caudatus seeds using an in vitro assay consisting of the inhibition of α‐amylase, which acts in the digestion of starch and reduces the absorption of glucose. Using streptozotocin‐induced diabetic rats, Kim and others (2006a,b) investigated the effect of amaranth oil and grain supplementation ( A. esculentus L.) on blood glucose and the lipid profile. The rats were divided into 4 groups: normal control, diabetic control, diabetic group supplemented with amaranth grain, and diabetic group supplemented with amaranth oil for 3 wk.…”
Section: Action On Blood Glucose Levelsmentioning
confidence: 99%
“…Besides the effects cited on the blood glucose levels, the work of Kim and other (2006a,b) also reported that feeding rats with either the whole grain or its oil resulted in an improvement (decrease) in the animals’ AST (aspartate aminotransferase) and ALT (alanine aminotransferase) enzymes, which are liver function markers. Moreover, there was a reduction in TBARS levels (thiobarbituric acid reactive substances, lipid peroxidation and oxidative stress indexes) in the liver cytosol.…”
Section: Effect On Liver Functionmentioning
confidence: 99%
“…A few reports have also indicated that amaranth contains peptides with inhibitory capacity against Dipeptidyl peptidase-IV (DPPIV), an incretin-degrading enzyme [11] and Angiotensin Converting Enzyme (ACE), a vasoconstriction-related enzyme [12]. Additionally, peptides with lipid-lowering [13] and antidiabetic activity have been reported [14]. However, the effect of the amaranth at a level of gene expression in adipose tissue has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of amaranth grain and oil failed to prevent weight loss but, significantly decreased the serum glucose, increased serum insulin levels, and decreased the levels of malondialdehyde (a marker of lipid peroxidation) [43]. The effect of amaranth on diabetic hyperlipidemia could be through its control of hyperglycemia [44]. Total cholesterol and triglyceride (TG) concentrations in liver and serum, and VLDL serum levels were significantly higher in STZdiabetic rats than normal control animals, supplementation of amaranth oil and grain suppressed the increase in these parameters in diabetic rats [44].…”
Section: Anti-diabetic and Anti-hyperlipidemic Effects Of Amaranth Comentioning
confidence: 99%